St. Vincent and the Grenadines : Report on Observance of Standards and Codes; FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2010)
This report was prepared by the Legal Department of the International Monetary Fund (IMF). It provides a summary of the Antimony Laundering and Combating the Financing of Terrorism (AML/CFT) measures in place in St. Vincent and the Grenadines (SVG) and of the level of compliance with the FATF 40+9 Recommendations, and contains recommendations on how the AML/CFT system could be strengthened. The assessment is based on the information available at the time of the mission. The preventive measures regime covers most of the financial and designated nonfinancial businesses and professions (DNFBP) sectors.